DETERMINAN CURAHAN TENAGA KERJA WANITA PADA USAHATANI PADI SAWAH DAN KONTRIBUSINYA TERHADAP PENDAPATAN KELUARGA DI KECAMATAN TALO KABUPATEN SELUMA - Risa Hardiana; Edi Efrita; Novitri Kurniati (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2022)
The phenomenon of female workers in the agricultural sector is not a new thing. Female farmers gave their labors to ricefield farming  to support  the head of  family to get earning income. This research was conducted to determine the factors that influence.This study was conducted to determine the factors that influence the outpouring of female workers in  ricefield farming and contribute to the income of farmer families in Talo District, Seluma Regency. This studyapplied Survey method and samples was taken by Simple Random Sampling method with a total sample of 84 female respondents who were ricefield farmers. Data analysis used Multiple Linear Regression analysis and income contribution. The results indicate that the factors that influenced the labor outpouring were age, family income, toddlers, and husband's main job, while education and family responsibilities had no significant effect. The average contribution of female rice farmers to family income in Talo District, Seluma Regency is low at 4 percent.